(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The rapid progress in the field of industrial and information-communication techno-logies and their impact on production systems are putting increasing pressure on the engineering structure. That is why modern technological deve-lopment has created conditions in which innova-tive obsolescence already takes precedence over physical. A particularly important point in this direction is the correct determination of the degree of influence of innovative aging on products and processes in order to establish its impact on the technical, economic and social results of industrial activity. In addition, the impact of this process is globalizing, resulting in innovative obsolescence of technology and lagging behind the level of advan-ced technologies from modern ones world-wide. The further use of innovatively obsolete equipment and technological processes leads to certain losses, the amount of which will depend on the degree of this lag. This report proposes an alternative approach to reducing the innovative obsolescence of industrial products by modernizing and creating sustainability in the engineering space. At the same time, innovative progress in the future will put increasing pressure on the technological structure and on the distinctive features of this process. A theoretical attempt has been made to calculate mathematically innovative aging, and the impact of destructive innovations is difficult to capture with this model.